PELATIHAN DAN PENDAMPINGAN PENGGUNAAN SISTEM INFORMASI PENGELOLAAN DATA PELANGGAN DI LERRY FASHION - Nunes, Ingratcia; Baun, Diandra; Sani, Michelle; Widiastuti, Tiwuk (Intimas, 2025)
Lerry Fashion, a tailoring business, faces challenges in managing customer data manually, leading to difficulties in record-keeping, increased risk of information loss, and slower data retrieval. This impacts operational efficiency and customer service quality. This study proposes the development of a computerized information system to address these issues, aiming to reduce errors, speed up data retrieval, and support strategic decision-making. The developed system is capable of recording and analyzing customer data more effectively, replacing the manual method, reducing the risk of data loss, and improving operational efficiency. User Acceptance Testing (UAT) shows a satisfaction level of 98%, indicating that the system is well-received by the owner and admin of Lerry Fashion. The implementation of this system is expected to serve as a reference for other small and medium-sized enterprises in effectively managing customer data, as well as improving performance and service through efficient use of information technology.